Design of wheeled chairs for assistance to elderly mobility - Hoong, Shi Xiang (Nanyang Technological University, 2020)
The wheelchair has been commonly used as solution to overcome mobility restrictions, especially in the healthcare, elderly care and people living with disability industry. From the time when the wheelchair was invented, the wheelchair has come a long way in terms of design to suit the needs of users. The wide array of wheelchair designs includes functions from being able to climb stairs to exoskeletal support in allowing the user to stand upright. With such innovative designs available, it is important for a novel wheelchair to cater to a specific need that has yet to be met. This project aims to increase the mobility of elderly by helping users overcome their dependency on a caregiver to move from bed to wheelchair and vice versa. The added feature is expected to reduce the physical burden of the caregivers when transferring the elderly to and from bed to wheelchair, where their fall risks can be greatly reduced. After many design considerations, the modified wheelchair is likely to greater improve the experience of elderlies with lower limb mobility limitations being transferred on and off the wheelchair with reduced fall risk. In conclusion, with the Singapore’s ageing population and trend of reducing ambulant ratio within the elderlies, this wheelchair design will greatly benefit the elderlies of the future.